What’s is the Current Situation about Health Care in the Maternity Facilities of Defense Forces in Benin? - Kpade, Agnès Angélique Houéfa; Olowo, Bénédicte Ingrid; Bothon, Romuald; Patinvoh, Tagnon Michel N.; Mariano, Efio; Léonce, Ahouanvoeke; Natacha, Nouwakpo; Raliatou, Amadou Djibril (British Journal of Healthcare and Medical Research, 2025)
Introduction: Still with this aim of extending this approach to other health centers, UNICEF supported "optimized care" on the maternity wards of the health centers of the Defense and Security Forces (FDS). As part of the implementation of optimized care in the mother-child services of the FDS, it was necessary to carry out an initial assessment in order to train staff on good practices. The main objective of this study was to assess the quality of maternal -child health care in the health centers of the FDS. Materials and Methods: It was devoted to training investigators on data collection techniques and tools. The training was led by a team of trainers from the Beninese Armed Forces (gynecologist, pediatrician) supported by UNICEF resource persons and national facilitators. Data collection was carried out by investigators in the four (04) health centers in the northern zone and three (03) in the southern zone with the supervision of the FABs supported by UNICEF resource persons and national facilitators. The data collection tools were made available by UNICEF BENIN and included interview questionnaires, observation sheets, and counting sheets. Data analysis was done in an EXCEL data mask designed and made available by UNICEF BENIN. Results : These indicators are identified: Proportion of newborns who benefited from early breastfeeding within the first hour of birth: 89% ; Proportion of newborns receiving cord care during the first 48 hours with chlorhexidine gel: 33% ; Availability of resuscitation equipment and standard newborn care supplies : 62% ; Rate of use of CPN 4 by qualified personnel : 75% ; Percentage of SONUB functions offered by the center: 86% ; Percentage of SONUB functions correctly implemented by the center: 60%. Conclusion: At the end of this preliminary study, it is important to set up an improvement plan based on the identified defects. This will contribute to improving the quality of care provided there.